Does Pandemic Crisis Mean Education Crisis? The Chicago Academic Plastic Surgery Collaborative Response to COVID-19. Issue 6 (10th May 2021) - Siotos, Charalampos; Reid, Russell R.; Corcoran, Julia F.; Ko, Jason; Agnew, Sonya P.; Dorafshar, Amir H.
Abstract : Supplemental Digital Content is available in the text. Abstract : Summary: The health care crisis related to the spread of novel coronavirus (severe acute respiratory syndrome coronavirus 2) has created new challenges to plastic surgery education, mostly because of the decreased volume of procedures. The plastic surgery program directors in Chicago decided to act and identify ways to promote surgical education through citywide, multi-institutional, systematic clinical case discussions. Although the initiative has no impact on the surgical skill of the trainees, it was welcomed by residents and faculty and promoted clinical core knowledge in plastic surgery and collaboration among the institutions.